Toleransi Penundaan Prosesing Terhadap Mutu Fisik dan Mutu Fisiologis Benih Kedelai (Glycine max L. Merril) - ROBERTO BOBHOPE ARUAN; I DEWA NYOMAN NYANA; I KETUT SIADI; I GUSTI NGURAH RAKA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Tolerance of Processing Delay to Physical and Physiological quality of Soya Bean (Glycine max L. Merril) The aim of this research is to figure out the time of the tolerance processing delay so that the physical quality and the physiological quality of soya bean seeds could be defended. This research was started in April 2017 at Jalan Cekomaria, Denpasar and also at the Lab. Pemuliaan Tanaman dan Teknologi Benih Faculty of Agriculture Udayana University. The design method was used for this research is a randomized complete block design (RCBD) using five treatment and five-time repetitions consist of W0= Without using process, W1= 1 day of Delaying process W2= 2 days of Delaying process, W3 = 3 days of Delaying process, W4 = 4 days of Delaying process. The statistic test and analyzing variance statistical test shows different result, the procedure followed by LSD method (Least Significance Different) with 95% of confidence level using costat program.The result of physical analysis test, shows that the role of the seeds which is without delaying process showing that the percentage of the seeds was 87,36% and the result of 4 days delaying process seeds are 11,256%. The result of the physiological test of the seeds using germinating test was, W0 (95,16%) and W4 (94,72%). The percentage of the vigor will be decreasing, which is W0 (80,52%) and W4 (34,4%). The equality control of the percentage was W0 (90,3%) and W4 (70,68%). Result of the observation of electrical conductivity showing that the lowest point of the electrical conductivity control is W0 (5,112 ? mhos cm¯² g¹) and the highest value of electrical conductivity was shown on the W4 (7,302 ? mhos cm¯² g¹).